Mono-metallic, Bi-metallic and Tri-metallic Biogenic Nanoparticles Derived from Garlic and Ginger with their Applications - Saba, Farooq; Munawar, Ali Munawar; Zainab, Ngaini (Bentham Science Publishers, 2023)
Biogenic metallic nanoparticles (NPs) produced from garlic and ginger have a wide range of applications in the pharmaceuticals, biotechnology and electronics industries. Despite many commercial NPs reported, NPs made from natural extracts are more affordable, straightforward and environmentally friendly than synthetic ap-proaches. Biogenic metallic NPs derived from garlic and ginger have superior biocompatibility, better dispersion, higher stability, and stronger biological activities. This is due to the fact that garlic and ginger possess significant activities against multi-drug resisted pathogens and are in high demand, especially for the prevention of microbial diseases. This review placed a substantial emphasis on comparative investigations of the synthesis of mono-, bi-, and tri-metallic NPs with a variety of sizes and forms, as well as applications using materials like ginger and garlic. The benefits and drawbacks of mono-metallic, bi-metallic, and tri-metallic biogenic NPs produced from garlic and ginger are also comprehensively highlighted. Recent improvements have opened the way to site-specific targeting and drug delivery by these metallic NPs.